Hippocampal Shape Analysis in Status Epilepticus Associated with Acute Encephalitis - Kaiboriboon, Kitti (AJNR Am J Neuroradiol, 2002)
Summary: We performed MR imaging deformation-based hippocampal shape analysis in a 28-year-old woman in whom status epilepticus developed after acute encephalitis. Hippocampal shape analysis revealed severe global bilateral hippocampal atrophy. Regional volume loss was most accentuated in the medial and lateral aspects of the hippocampal head; the loss was similar to shape changes in hippocampal sclerosis of chronic temporal lobe epilepsy. This deformation pattern may reflect a common pathologic process that causes hippocampal volume loss in both of these conditions.